2022
DOI: 10.3390/ijms231810694
|View full text |Cite
|
Sign up to set email alerts
|

Root-Zone CO2 Concentration Affects Partitioning and Assimilation of Carbon in Oriental Melon Seedlings

Abstract: Root-zone CO2 is essential for plant growth and metabolism. However, the partitioning and assimilation processes of CO2 absorbed by roots remain unclear in various parts of the oriental melon. We investigated the time at which root-zone CO2 enters the oriental melon root system, and its distribution in different parts of the plant, using 13C stable isotopic tracer experiments, as well as the effects of high root-zone CO2 on leaf carbon assimilation-related enzyme activities and gene expressions under 0.2%, 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Fatty acid methyl esters have strong a nity for ester compounds and can be used as herbicides and herbicide carriers to remove weeds (Sati et found that different times and different concentrations of CO 2 treatments affected the rate of 13 C uptake in the root zone of oriental melon seedlings and altered the assimilation and distribution of 13 C in stems and leaves (Han et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid methyl esters have strong a nity for ester compounds and can be used as herbicides and herbicide carriers to remove weeds (Sati et found that different times and different concentrations of CO 2 treatments affected the rate of 13 C uptake in the root zone of oriental melon seedlings and altered the assimilation and distribution of 13 C in stems and leaves (Han et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…13 C stable isotope tracer technology is an effective means to research the mode of action of allelopathic substances on plants (indirect or direct action) and the dynamic changes of uptake, transport, synthesis and distribution in plants and the strength of allelopathic inhibition in different parts of the plant, and further reveal the allelopathy mechanism of allelochemicals inhibiting the growth of invasive weeds 29 31 . Han et al found that different times and different concentrations of CO 2 treatments affected the rate of 13 C uptake in the root zone of oriental melon seedlings and altered the assimilation and distribution of 13 C in stems and leaves 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Method (i) applies the high abundance 13 C labeling and then calculates the ratio of soil DIC fixed in specific tissues or organs to the total carbon gain. The total carbon gain includes soil DIC fixation, apparent photosynthesis measured by commercial infrared gas analyzers, and respiration [20,28]. However, this calculation is not directly linked to photosynthesis.…”
Section: Introductionmentioning
confidence: 99%